Cathodal tDCS Guided by Thermography as Adjunctive Therapy in Chronic Migraine Patients: A Sham-Controlled Pilot Study - Dalla Volta, Giorgio; Marceglia, Sara; Zavarise, Paola; Antonaci, Fabio (Frontiers in Neurology, 2020)
Objective: To explore the efficacy of cathodal tDCS applied ipsilateral to the cold patch, as determined by thermographic evaluation, in the treatment of chronic migraine. Background: Transcranial direct current stimulation (tDCS) is a non-invasive and safe technique that modulates the activity of the underlying cerebral cortex. tDCS has been extensively tested as a possible treatment for chronic pain and migraine with controversial results mainly due to the different setting procedure and location of electrodes. Since the presence of a hypothermic patch region detected through thermography has been suggested as a possible support for headache diagnosis, this “cold patch” could considered as possible effective location for tDCS application. Methods: Forty-five patients with chronic migraine were randomized to receive either cathodal (25 patients) or sham tDCS, for 5 consecutive daily sessions plus a recall session after 1 month. Cathodal tDCS was delivered at 1.5 mA for 15 min in each session. Subjects were evaluated before treatment (baseline, T0), and after 10 (T10), 60 (T60), and 120 (T120) days after treatment. The number of attacks, duration of attacks, pain intensity, number of days with headache, and number of analgesics were collected at each time evaluation. Results: Patients in the tDCS group showed a significant improvement compared to the sham group, during the whole study period in the frequency of migraine attacks (tDCS vs. sham: −47.8 ± 50.1% vs. −14.2 ± 16.5%, p = 0.004), number of days with headache (tDCS vs. sham: −42.7 ± 65.4% vs. −11.3 ± 18.0%, p = 0.015), duration of attacks (tDCS vs. sham: −29.1 ± 43.4% vs. −7.5 ± 17.6%, p = 0.016), intensity of the pain during an attack (tDCS vs. sham −31.1 ± 36.9% vs. 8.3 ± 13.5%, p = 0.004), and number of analgesics (tDCS vs. sham −54.3 ± 37.4% vs. −16.0 ± 19.6%, p < 0.0001). Conclusion: Our results suggest that cathodal tDCS is an effective adjuvant technique in migraine provided that an individual correct montage of the electrodes is applied, according to thermographic investigation.